Efficacy of idebenone in the Treatment of iRBD into Synucleinopathies (EITRS): rationale, design, and methodology of a randomized, double-blind, multi-center clinical study - Li, Yuanyuan; Wang, Chunyi; Luo, Ningdi; Chen, Fangzheng; Zhou, Liche; Niu, Mengyue; Kang, Wenyan; Liu, Jun (Frontiers in Neurology, 2022)
Background: As the strongest prodromal marker of α-synuclein-specific neurodegeneration, idiopathic REM sleep behaviour disorder (iRBD) is becoming a focus of interest in disease-modifying therapy. Idebenone has been widely portrayed as a potent antioxidant targeting mitochondrial dysfunction. Previous study has identified the effect of idebenone on Parkinson’s disease with promising outcomes by regulating mitophagy. A novel indication of idebenone should be highlighted in iRBD population. Methods: The EITRS study is a randomized, double-blind, multi-center clinical study assessing the efficacy and safety of idebenone in the treatment of iRBD into synucleinopathies. 142 patients (aged 40-75 years old) with clinically diagnosed iRBD are planned to be recruited with 80% statistical power and randomly assigned to idebenone (30 mg each time, three times a day) or matching placebo orally for five years. The assessment of rating scales, blood testing and neuroimaging examinations will be conducted at baseline, the 1st, 3rd and 5th year of follow-up. The primary efficacy endpoint is the 5-year conversion rate in patients with iRBD. The secondary endpoint is the safety and tolerability of idebenone in the treatment of iRBD. The study has been launched in July 2020. Discussion: This is the first prospective study designed to identify the efficacy and safety of idebenone on the treatment of iRBD into synucleinopathies. The current results are expected to promote the development of evidence-based recommendations for the management of patients with iRBD. Furthermore, we hope to provide insights on a possible disease-modifying approach with robust evidence.